MODEL PENINGKATAN KOMITMEN ORGANISASI BERBASIS PADA KNOWLEDGE SHARING, LEADERSHIP DAN KOMPENSASI - Natoil Natoil; Yovita Mumpuni Hartarini; Warsilan Warsilan (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
This study aims to examine the effect of knowledge sharing, leadership and compensation and their impact on organizational commitment. The problem in this research is how to increase organizational commitment in the Karangjati Business Development Cooperative. In this study, the population used was all cooperative employees, totaling 34 people. Regression analysis was run using Statistical Package Social Science (SPSS) software, which was used to analyze the data. The results of the analysis showed that knowledge sharing, leadership and compensation had a significant effect on organizational commitment. These empirical findings indicate that knowledge sharing on employee organizational commitment shows a t-count value of 4,239, leadership shows a t-count value of 3,418 and compensation shows a t-count value of 4,966 which has a significant effect on organizational commitment.